2007
DOI: 10.1029/2007gl030474
|View full text |Cite
|
Sign up to set email alerts
|

Convergent blooms of Karenia brevis along the Texas coast

Abstract: A numerical model of wind‐driven surface flow in the Gulf of Mexico is used to examine physical controls on harmful algal bloom formation along the Texas coast. Karenia brevis, which blooms frequently in the Gulf of Mexico, has a relatively slow growth rate (doubling times of 2–3 days). Increases in K. brevis concentration cannot be explained simply in terms of growth. We hypothesize that the primary mechanism responsible for bloom formation in the western Gulf of Mexico is convergence due to downwelling at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…Thyng et al (2013) found that a weak downcoast mean alongshore wind velocity for the month of September was required for bloom formation along the coast of Texas. This result was in agreement with the results of Hetland and Campbell (2007) in showing that downwelling at the coast can result in a coastal aggregation of spatially dispersed cells. The model results in this paper suggest subsurface cells are advected north toward the coast of Texas during the summer months and can provide an above background concentration seed population for a fall bloom.…”
Section: Reverse Runssupporting
confidence: 94%
See 2 more Smart Citations
“…Thyng et al (2013) found that a weak downcoast mean alongshore wind velocity for the month of September was required for bloom formation along the coast of Texas. This result was in agreement with the results of Hetland and Campbell (2007) in showing that downwelling at the coast can result in a coastal aggregation of spatially dispersed cells. The model results in this paper suggest subsurface cells are advected north toward the coast of Texas during the summer months and can provide an above background concentration seed population for a fall bloom.…”
Section: Reverse Runssupporting
confidence: 94%
“…Previous work revealed no genetic differentiation among blooms from Florida and blooms from Texas and it was hypothesized that bloom-forming cells in Florida and Texas originate from the same source yet the location of the source population remained unknown . Blooms of K. brevis off the coast of Texas appear to be the product of widely dispersed cells accumulating by physical concentration (Hetland and Campbell, 2007;Stumpf et al, 2008). The combination of low background cell concentrations and the physical accumulation of cells suggests blooms could occur randomly throughout the year; however, this is not the case.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is where tidal mixing is at a minimum (He and Weisberg, 2002) and a transport barrier reduces mixing between inshore and offshore waters Olascoaga et al, 2006;Olascoaga, 2010). In Florida, Texas, and Mexico, K. brevis is most likely to form blooms in the fall months Steidinger et al, 1998;Brand and Compton, 2007;Hetland and Campbell, 2007). Hetland and Campbell (2007) have shown that downwelling during the fall months along the Texas coast can lead to a 1000-fold concentration of K. brevis cells, making it a likely factor in the development of blooms there.…”
Section: K Brevis In the Gulf Of Mexicomentioning
confidence: 96%
“…The most obvious case is downwelling, in which cells at the surface from a large area are transported to the downwelling site and accumulate there as they swim upward to counteract the downward movement of the water. Over time, this mechanism can generate very high concentrations of organisms (Hetland and Campbell, 2007).…”
Section: Bloomsmentioning
confidence: 99%